DESAIN PEMBELAJARAN: Potret Profesionalitas Dosen - Askar Ahmad (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2007)
The professional lecturer has to own some compe-tences such as pedagogical, personal, professional, and social compe-tence. Pedagogical competence is the ability to manage the students to learn. To manage the learning well, it must be begun with activity in order to plan and design the learning. The design of learning consist of the formulation of the objective of learning which will be achieved, the development of the learning material or subject matter, it should be suitable with the objective of learning will be achieved, formulate the strategy and the learning method, and also design of the learning media which supports the achievement toward the objective of the learning, as well as evaluate so that to measure the lesson achievement whether the process or its result. The ability to design the learning is one of decision factors which support the level of lecturer’s profession.